THE DISCOURSE OF INDONESIAN FIQH Methodological Bid of Family Law Reform - Wahid, Marzuki (Al-Mawarid Jurnal Hukum Islam, 2015)
The following article discusses the methodology bid and that of family law reform. This discussion is an affirmation that the Indonesian fiqh which is constructed based on reality Indonesia. Most of the Indonesian fiqh still littered the pages bahtsul masaâil decision, the Majlis Legal Affairs Committee, the board hisbah, MUIâs fatwa, and in the form of motion religiosity Indonesiaâs diverse Muslim communities. Others fiqh of Indonesia have entered into a state structure, which is a positive law. Fiqh Indonesia as positive law is a political and social construction, not merely theological formulation, but also the factors of non-theological is a logical consequence of the building fiqh who live in the midst of true nation-state based on Pancasila and justified by the stateâs political decision , Therefore, approved or rejected a formulation of Islamic law in the legislative process is not as theologically correct or incorrect, but because of the victory of the political configuration and the dominant actors who are able to influence the legislature and the Government as the legislators and the public as a support group or a suppressor. On that basis, the creation of a public space free (free public sphere), controversy or public debate about Indonesian fiqh is actually very productive. In this debate konterks Shariâah understood in the context of Indonesian-ness, defined and redefined in the public space nationality how Shariâah take a constructive role in the big house Pancasila. Keywords : Methodology, Indonesian Fiqh, Islamic Family Faw, and Reform.